The relationship between region of residence, socio-demographic factors, and healthcare utilization among Saudi citizens: insights from the 2013 Saudi Health Interview Survey - Aljohani, Motab; Donnelly, Michael; Al Sumaih, Ibrahim; O'Neill, Ciaran (Frontiers in Medicine, 2023)
There is a dearth of research on the nature and extent of variation in patterns of health service use in Saudi Arabia This is an important gap in our knowledge given ongoing efforts to improve service provision. The aim of this study was to examine the impact of Region and Socio-Demographic Factors on the patterns of health service use in Saudi Arabia. Methods Data were taken from 2013 Saudi Health Interview Survey (SHIS), a national multistage survey of individuals aged 15 and over in Saudi Arabia. Data included measures of service use, respondent health, socio-demographic characteristics, and region of residence. Descriptive statistics, Chi-square tests, and multivariable logistic regression analyses were used to describe the data and examine the relationship between the likelihood of a visit to a doctor or healthcare professional in the preceding 12 months. The sample was also partitioned by region to examine the role of health and socio-demographic characteristics within selected regions. Results The likelihood of visiting a doctor or health care professional was related to poor health status, being female, married, having a low income and region in which respondents resided. Respondents aged less than 65 and those who lived furthest from service providers, were less likely to visit a doctor or other health professional (P<0.01). Residents who lived in Riyadh, Al Medina, Baha, or Aseer demonstrated a higher likelihood of service utilisation compared to respondents residing in other regions(p<0.05). In sub-group analyses, there was variation between regions with respect to socio-demographic status and distance to service. Conclusion Region and income help to explain the likelihood of primary care use in Saudi Arabia and the distinct patterns between region and socio-demographic characteristics. It is likely that service utilisation differences related to the socio-demographic characteristics of respondents reflect differences in pre-disposing and enabling factors in the ABM. Differences in terms of population need, enabling and predisposing factors may explain the between-region variation in service use. The findings underscore the importance of considering region or area of residence when seeking to understand utilization of health services, particularly primary care services.